Modelling the Effect of Environmentally Sustainable Food Substitutions on Nutrient Intake in Pregnant Women - Wang, Tian (Curr Dev Nutr, 2021)
OBJECTIVES: Adopting environmentally sustainable diets can substantially reduce anthropogenic greenhouse gas emissions (GHG). However, there remain concerns that consuming sustainable foods will increase the likelihood of nutritional deficiencies in periods of increased demand, including pregnancy. This study aimed to identify commonly consumed foods of pregnant women and determine the effect of their replacement with sustainable alternatives on nutrient intake and measures of environmental sustainability. METHODS: Dietary intake data from 171 pregnant women were assessed using a validated food frequency questionnaire. The food groups and food items that contributed most to energy and protein intake were identified. Of these foods, those that produce the highest GHG emissions (Poore et al. 2018) were matched with proposed sustainable alternatives for energy and protein content, and their impact on nutrient provision and sustainability measures were determined. RESULTS: Meats (bovine, poultry, fish, lamb and eggs), grains and dairy products were important sources of both energy and protein intake. With the highest GHG emissions, beef was selected as the reference food. Proposed food alternatives included lamb, chicken, eggs, fish, tofu, legumes and nuts. The most pronounced reductions in CO(2) emission were from replacing beef with tofu, legumes and nuts. For example, replacing one serve of beef with an isocaloric serve of firm tofu per week during pregnancy could reduce GHG emissions by 372 kg CO(2) eq, equivalent to that produced by an average passenger vehicle driving 1498 km. This replacement would not adversely impact iron (+1.1mg per serve) content, whilst providing a richer source of calcium (+294.8mg per serve), folate (+28.1µg per serve) and dietary fibre (+3.3g per serve). A once-weekly substitution of animal-derived foods for more sustainable plant-based alternatives within the context of a mixed diet has minimal effect on overall nutrient intake. CONCLUSIONS: Simple dietary substitutions, as little as replacing one serve of red meat with sustainable alternatives weekly, can substantially reduce environmental impact without compromising nutrient adequacy. These sustainable food replacements should be the focus of future applied clinical research. FUNDING SOURCES: No funding support for conducting this project was received.